Early detection and management of white uust disease (Albugo candida) in rapeseed-mustard - Kalpana Gairola; AK Tewari (Journal of Oilseed Brassica, 2026)
The early detection of Albugo candida was done by PCR-based assay and light microscopy. In PCR based assay theprimers ITS1 (3’-GAGGGACTTTTGGGTAATCA-5’) and Short ITS JV34 (3’-CGCCATTTAGAGGAAGGTGA-5’) andJV37 (3’-GTCAAGCAAAACAT-5’) were used to amplify the ITS region of A. candida and Alternaria brassicae. PCRamplification of A. candida from inoculated symptomatic and asymptomatic leaves yielded PCR products of 1200 bp and600 bp of ITS1 and Short ITS primers, respectively whereas no bands were amplified in A. brassicae. This confirmed thepresence of A. candida in asymptomatic inoculated leaves at early stages i.e. 1, 2, 3, 4, 5 and 6 days after inoculation(DAI). In light microscopy the presence of pathogen structures were observed from inoculated symptomatic andasymptomatic inoculated leaves. The presence of pathogen structure viz. mycelium and sporangia was observed inasymptomatic leaves at early stages i.e. at 6,7,8 and 9 DAI ,in symptomatic leaves at 10 and 11 DAI and no fungalstructures in healthy mustard leaves after staining with 1 percent cotton blue in lacto phenol and 0.4% trypan blue.During evaluation of rapeseed-mustard germplasm it has been observed that some Brassica germplasm escaped fromthe white rust disease in field found susceptible in glasshouse at both the stages (EC-399299) or only at true leaf stage(Katili local, Eruca sativa, Basanti and Banarasi rai, PWR-14-8, PWR-14-9, PWR-14-10, PWR-14-11, RMT-1-10-1, IC597942 and IC265495). The study revealed that for the confirmation of resistant sources, it is very essential to evaluateBrassica germplasm first in field and then in glasshouse at both the stages i.e. at cotyledonary and true leaf stage underhigh disease pressure. Among various fungicides Metalaxyl 8% + Mancozeb 64% (Ridomil MZ @ 0.25%) and a biologicalorigin Azoxystrobin (Amistar 25 EC @ 0.1%) were found highly effective in inhibiting sporangial germination in-vitroand in controlling white rust disease (no occurrence of disease) in glasshouse and in field.